Peningkatan Minat Belajar Peserta Didik dengan Penerapan Apersepsi Visual Menggunakan Model Problem Based Learning - Nafin Nihayati; Muh Said; Wahyuningsih Wahyuningsih (UNIVERSITAS NEGERI MAKASSAR, 2022)
Students' interest in learning to take part in learning is a fundamental thing that affects the learning process. Students who have a high interest in learning in the learning process can support the learning process to be better and more active. Based on the observations found by the author based on observational data, the teacher uses a conventional model (lecture) which causes students' low interest in learning to follow the learning process. There are 17 or 36% of students showing interest in learning process. The rest of the students' interest in learning is low. This is due to the lack of attractive learning methods applied by teachers in the learning process activities. Through innovation with the application of visual apperception by applying the PBL (problem based learning) model, it showed a fairly good increase in student interest in learning in class VIII on social mobility material. The results showed that the data on increasing student interest in learning by applying visual apperception using the Problem Based Learning model were 42 students or 88% who showed interest in learning in social mobility lessons. This proves that providing visual apperception is very important so that it can increase student interest in learning in class VIII of SMP Negeri 7 Kunto Darussalam.AbstrakMinat belajar siswa mengikuti pembelajaran adalah hal mendasar yang mempengaruhi proses pembelajaran. Siswa yang mempunyai minat belajar tinggi dalam proses pembelajaran dapat menunjang proses pembelajaran untuk semakin baik dan aktif. Berdasarkan pengamatan yang ditemui penulis berdasarkan data observasi, guru menggunakan model konvensional (ceramah) yang menyebabkan rendahnya minat belajar siswa dalam mengikuti proses pembelajaran. Terdapat 17 siswa atau 36% siswa memperlihatkan minat belajarnya dalam proses pembelajaran. Sisanya minat belajar siswa rendah. Hal ini di karenakan kurang menarik metode pembelajaran yang diterapkan guru dalam kegiatan proses pembelajaran. Melalui inovasi dengan penerapan apersepsi visual dengan menerapkan model PBL (problem based learning) menunjukkan peningkatan yang cukup baik pada minat belajar siswa dikelas VIII pada materi mobilitas sosial. Hasil penelitian menunjukkan data peningkatan minat belajar siswa dengan diterapkan apersepsi visual menggunakan model Problem Based Learning sebanyak 42 siswa atau 88% yang menunjukkan minat belajarnya pada pelajaran mobilitas sosial. Hal ini membuktikan bahwa memberikan apersepsi visual sangatlah penting sehingga dapat meningkat minat belajar siswa di kelas VIII SMP Negeri 7 Kunto Darussalam.